PREVALENCE OF TREMATODES IN JAVAN RHINOCROS AND BANTENG IN UJUNG KULON NATIONAL PARK - Tiuria, Risa; Pangihutan, Jimmy; Mustafa Nugraha, Ripta; Pontjo Priosoeryanto, Bambang; Rahmat Hariyadi, Adhi (Jurnal Veteriner; Vol 9 No 2 (2008), 2008)
Javan rhinoceros (Rhinoceros sondaicus) and Javan bull (Bos javanicus) in National Park Ujung Kulon are protected wild animals. A study to examine the presence of trematode eggs in their fecal samples was carried out. The fecal samples were collected based on the transec route in National Park Ujung Kulon. The presence of eggs in fecal samples was examined by filtration method. Trematode eggs were found in 56% of Javan rhinoceros fecal samples and 73,91% of Javan bull fecal samples.. Base on the size of the eggs it was determined that Javan bulls in National Park of Ujung Kulon were infected by Fasciola spp (17,39%) and Paramphistomum spp (56,52%). Javan rhinoceros in National Park of Ujung Kulon was infected with Fasciola spp (44%) and Schistosoma spp (12%). This study clearly showed that tramatode infection is commom among wild ruminants in Ujung Kulon National Park and attention should be taken to improve the health status of the animals especially Javanese rhinoceros and Javanese bull
Keywords: Javan rhinoceros, Javan bull, trematoda parasitic